The profile of the physiotherapy professional working in the unit of intensive care: Integrative review (Research, Society and Development, 2021)
The study on the profile of the physiotherapy professional who works in the intensive care unit in Brazil is relevant to enable a broad knowledge of who these professionals are and thus develop mechanisms that help them in the labor and intellectual fields. The objective was to know the profile of physical therapists working in the intensive care unit in Brazil from their sociodemographic and professional portrait. It was an integrative review developed from November 2020 to February 2021, using the search strategy "Physiotherapy", "Hospital Physical Therapy Service" and "Intensive Care Units", performing the interaction between the descriptors through the Boolean AND operator. A scenario of professionals of both sexes, mostly women, was identified. There was a need for further academic development after graduation. Most have specialization in cardiorespiratory. It was seen that the portrait of professionals working in physiotherapy in an intensive care unit in the country is satisfactory, but permanent specialization in the area is needed, as well as improvement in the guarantees of rights and valuation of work.